Synthesis How Teachers Assess Students’ Level Understanding In Learning Science Through Learning Expressions - Debby Fidtriani Sukma (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2024)
The way teachers recognize students' level of understanding in learning science can be done through learning expressions. This is very important because science education is not just about memorizing words, but also understanding concepts and applying knowledge in relevant contexts. This research aims to synthesize the various methods used by teachers to recognize students' level of understanding through their learning expressions. In the context of classroom learning, identifying students' level of understanding is an important aspect to ensure the effectiveness of teaching and achieving optimal learning outcomes. This research uses qualitative methods. Data collection techniques are carried out by observation and interviews. The research results show that teachers can recognize students' level of understanding through various learning expressions, such as body language, facial expressions, eye contact, and students' verbal responses.